The role and task of the medical social worker in a rehabilitation setting : an evaluation of selected patients at the Rehabilitation Clinic, Karl Bremer Hospital, Bellville - Hanekom, Anita (Department of Social Development, 2016)
Bibliography: pages 178-181.